COLLECTIVE HUMAN RESURRECTION IN MODERN SECULAR FANTASTIC AND SPECULATIVE FICTION: AN OVERVIEW - Mariano Martín Rodríguez (Universitat Autònoma de Barcelona, 2018)
It would be a complete «revolution» (etymologically a turn-around) if death were defeated and the deceased returned to the world as they were, in the flesh and with their own individuality, instead of coming back as reanimated monsters. This fantastic possibility is usually described as having revolutionary existencial and societal effects, since the society and the emotional lives of the living is usually transformed through the contact with the returned, whose very presence seems to alter the meaning of life. This paper provides an overview of resurrection stories by international writers, from Giacomo Leopardi to some modern classics, such as Tudor Arghezi, Érico Veríssimo, Marcel Thiry, Angélica Gorodischer and Robert Silverberg, as well as by others less well known, in a variety of fictional works on this matter, especially in the fantastic, but also in the speculative mode.